2021
DOI: 10.1021/acssuschemeng.1c03528
|View full text |Cite
|
Sign up to set email alerts
|

Role of β-CD Macromolecule Anchored to α-Fe2O3/TiO2 on the Selectivity and Partial Oxidation of Guaiacol to Add-Value Products

Abstract: Biomass is a naturally abundant, sustainable, and clean resource, which has the potential to replace fossil feedstock for sustainable production of high add-value chemicals. However, an efficient conversion process is still difficult to achieve due to the difficult reaction conditions. In this study as a novel and versatile concept, we introduced the use of β-cyclodextrin (β-CD) macromolecule to enhance the photocatalytic behavior of a α-Fe 2 O 3 /TiO 2 heterojunction. The selective conversion of guaiacol was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Previous reports have shown that guaiacol photocatalytic oxidation may occur through different mechanisms involving reactive oxygen species such as ⋅OH, O 2 ⋅ − and ⋅OOH, among others [13,68–70] . Conversion rates shown in Table 4 indicate that photocatalytic conversion of guaiacol relays in more than one reactive oxygen species.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous reports have shown that guaiacol photocatalytic oxidation may occur through different mechanisms involving reactive oxygen species such as ⋅OH, O 2 ⋅ − and ⋅OOH, among others [13,68–70] . Conversion rates shown in Table 4 indicate that photocatalytic conversion of guaiacol relays in more than one reactive oxygen species.…”
Section: Resultsmentioning
confidence: 95%
“…Previous reports have shown that guaiacol photocatalytic oxidation may occur through different mechanisms involving reactive oxygen species such as * OH, O 2 *À and * OOH, among others. [13,[68][69][70] Conversion rates shown in Table 4 indicate that photocatalytic conversion of guaiacol relays in more than one or * OOH for these photocatalyst. Both samples produce hydroquinone (A3), indicating that the main reaction pathway for its production was through O 2 *À or * OOH.…”
Section: Photocatalytic Conversion Of Guaiacolmentioning
confidence: 99%
“…The peak at 3428 cm À1 is associated with the stretching and bending vibrations of the O-H groups (hydroxyl and chemisorbed water). 24,25 The peaks at 2924 and 1736 cm À1 for the ORT are attributed to the stretching vibrations of C-H and C]O functional groups, respectively, 26,27 which are the characteristic groups of cellulose. The peaks at 1566 cm À1 for CRT are attributed to C]C vibrations and the peaks at 1028 cm À1 for ORT and CRT are attributed to C-O vibrations.…”
Section: Preparation Of Crt and Characterization Resultsmentioning
confidence: 99%
“…β-Cyclodextrin (β-CD) is essential in photogenerated charge transfer, as it can serve as a hole eliminator to suppress recombination of photogenerated (h + -e − ) pairs. It has also been shown that its presence contributes to a more selective reaction because it prevents the formation of the •OH radical, which is highly reactive but not selective, so its presence contributes to complete degradation reactions, obtaining as final products CO 2 and H 2 O [95,124].…”
Section: Photocatalysts Modified By Macromoleculesmentioning
confidence: 99%